KERJASAMA ANTARA PEMERINTAH, PERUSAHAAN DAN MASYARAKAT DALAM PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI KOTA BONTANG - Cathas Teguh Prakoso (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to find out and analyzethe implementation of Corporate Social Responsibility in Bontang. The potential industries apparently do not correlates to the prosperity of the people in which there are still poor families liveng. This research shows that the implementation of CSR is not effective because of these several things, limited regulations, assymetrical relations between corporation and society, and the uncoordinated mechanism of CSR